Estudo da aplicação do aterramento ressonante em redes de distribuição com ramais monofásicos e bifásicos - Frederico Branquinho Teixeira (2012)
The continuous search for better reliability indices in the power supply and the financial losses in the industrial processes, arising from power grid shutdowns, are among the reasons which make utilities and major industries always seek new technologies to improve their electrical systems. A grounding technique little used in Brazil, but in expansionin many countries in Europe and China, is the neutral grounding via Petersen coil or resonant grounding. In it, the neutral of the substation transformer is connected to the ground through a reactor whose reactance is defined to compensate the total phaseground capacitance of the entire network. On the occurrence of a phase-to-ground fault, a low amplitude current will ow through the point of failure, favoring arc self-extinction and system reestablishment in a few cycles without any supply interruption. This dissertation treats primarily the basic theory of resonant grounding. Then, the systems and the main technologies used along with the coil are presented. In the last chapter, by means of circuit simulations with typical characteristics of urban and rural distribution networks, some contributions are made to the study of the migration fromsolid grounding to resonant grounding in brazilian networks. The main topics studied were the impact of the presence of single-phase and two-phase branches, insulation coordination, high-impedance faults and broken wires, and the inuence of the saturable core coil.